Barducci's Hugo Grotius and the Century of Revolution, 1613-1718 - Klimchuk, Dennis (Locke Studies, 2022)
A review of Marco Barducci’s recent book Hugo Grotius and the Century of Revolution, 1613–1718 (Oxford: Oxford University Press, 2017).